Respostas

2014-05-06T22:24:48-03:00
A= 3 b= -7 c=2 
x = 7 ₊/₋ √-7² - 4. 3. 2
              2.3
x = 7 ₊/₋ √49  -24
               6
x = 7 ₊/₋ √25
            6
x= 7 ₊/₋ 5
          6
x' = 7 + 5 =  12 ÷ 6 = 2
         6         6          3
x'' = 7 -5 =   2  ÷ 2 = 1
          6       6          3



2 4 2
A melhor resposta!
2014-05-06T22:30:42-03:00
Fórmula:
Delta=b ^{2}-4.a.c
 \frac{b ^{2}+- \sqrt{Delta}  }{2.a}

3x²-7x+2=0
a=3    b=7    c=2

Delta=7 ^{2}-4*3*2 \\Delta=49-24\\Delta=25

x= \frac{-7+- \sqrt{25} }{2*3}\\\\x= \frac{-7+-5}{6}\\\\ x_{1}= \frac{-7+5}{6}= \frac{-2}{6}=-3  \\\\  x_{2}= \frac{-7-5}{6}=-2

1 5 1